Clinical Pathological Features and Current Animal Models of Type 3 Macular Neovascularization - Qiang, Wei; Wei, Ran; Chen, Yongjiang; Chen, Danian (Frontiers in Neuroscience, 2021)
Type 3 macular neovascularization (MNV3) or retinal angiomatous proliferation (RAP) is a distinct type of neovascular age-related macular degeneration (AMD), which is a leading cause of vision loss in older persons. During the past decade, systematic investigation into the clinical, multimodal imaging, histopathological features and therapeutic outcomes has provided important new insight into this disease. These studies favor the retinal origin of MNV3 and suggest the involvement of retinal hypoxia, inflammation，VHL-HIF-VEGF pathway and multiple cell types in the development and progression of MNV3. Several mouse models, including recently built Rb/p107/Vhl triple knockout mouse model by our group, have induced many of the histological features of MNV3 and provided much insight into the underlying pathological mechanisms. These models have revealed the roles of retinal hypoxia, inflammation, lipid metabolism, VHL/HIF pathway and Rb-E2f cell cycle pathway in the development of MNV3. This article will summarize the clinical, multimodal imaging and pathological features of MNV3, and diversity of animal models that exist for MNV3 as well as their strengths and limitations.